2006
DOI: 10.1161/01.res.0000246086.93555.f3
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Vasculopathy Versus Atherosclerosis

Abstract: Abstract-Over the last 4 decades, heart transplantation (HTx) has evolved as a mainstream therapy for heart failure.Approximately half of patients needing HTx have organ failure consequent to atherosclerosis. Despite advances in immunosuppressive drugs, long-term success of HTx is limited by the development of a particular type of coronary atherosclerosis, referred to as cardiac allograft vasculopathy (CAV). Although the exact pathogenesis of CAV remains to be established, there is strong evidence that CAV inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
215
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(232 citation statements)
references
References 133 publications
2
215
1
11
Order By: Relevance
“…Experimental data from mouse models have demonstrated that alloantibodies may induce the development of fibrous intimal thickening of coronary arteries, a hallmark of human cardiac allograft vasculopathy (CAV). CAV is a multifaceted disease (8)(9)(10), with a complex pathophysiology involving either nonimmune and/or immune factors (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data from mouse models have demonstrated that alloantibodies may induce the development of fibrous intimal thickening of coronary arteries, a hallmark of human cardiac allograft vasculopathy (CAV). CAV is a multifaceted disease (8)(9)(10), with a complex pathophysiology involving either nonimmune and/or immune factors (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…ISHLT issued a consensus statement in 2010 stating that coronary angiography in conjunction with assessment of cardiac allograft function is likely to detect CAV with high degree of confidence [20]. Despite pathological differences, CAV and traditional coronary artery disease (CAD) do share some similarities and have some common contributing factors (Table 2) [10,[21][22][23]. Immunologic factors play a major role in the development of graft coronary artery disease (GCAD) or CAV, while metabolic and genetic factors play a dominant role in the development of traditional CAD.…”
Section: Definition and Diagnosismentioning
confidence: 99%
“…The characteristic lesions that are seen in CAV are also noted in other solid organ transplants such as kidney, liver, and lung [24][25][26]. CAV is not a homogenous disease and lesions may vary morphologically ranging from lipid-rich atherosclerotic plaques to fibrointimal proliferation of the allograft vasculature [10,17,21,22]. The atherosclerotic lesions seen in the allografts can be either donor derived lesions or de novo lesions developed after transplantation.…”
Section: Definition and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations